2017
DOI: 10.1103/physrevb.96.075103
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and electrical transport in metals and superconductors across antiferromagnetic and topological quantum transitions

Abstract: We study thermal and electrical transport in metals and superconductors near a quantum phase transition where antiferromagnetic order disappears. The same theory can also be applied to quantum phase transitions involving the loss of certain classes of intrinsic topological order. For a clean superconductor, we recover and extend well-known universal results. The heat conductivity for commensurate and incommensurate antiferromagnetism coexisting with superconductivity shows a markedly different doping dependenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 68 publications
5
18
0
Order By: Relevance
“…1) of phases where the electron fractionalizes into an electrically charged gapless fermionic chargon and a gapped charge-neutral spin-carrying spinon [3]. Such a phase of matter has topological order [4], and has been previously discussed in the context of the pseudogap metal [5][6][7][8][9][10]. Indeed, model calculations of the longitudinal conductivities and the electrical Hall conductivity in these fractionalized phases [5] are consistent with experimental observations in the metallic phases of several cuprates.…”
Section: Introductionsupporting
confidence: 74%
“…1) of phases where the electron fractionalizes into an electrically charged gapless fermionic chargon and a gapped charge-neutral spin-carrying spinon [3]. Such a phase of matter has topological order [4], and has been previously discussed in the context of the pseudogap metal [5][6][7][8][9][10]. Indeed, model calculations of the longitudinal conductivities and the electrical Hall conductivity in these fractionalized phases [5] are consistent with experimental observations in the metallic phases of several cuprates.…”
Section: Introductionsupporting
confidence: 74%
“…Of course, it can be reconciled with the theory by assuming a suitable doping-dependent enhancement of the scattering rate below p * . 9,12 A pronounced temperature and doping-dependent inplane anisotropy (nematicity) of the longitudinal conductivities has been observed in YBCO by Ando et al 55 The maximal conductivity ratios σ yy /σ xx observed in these experiments are much larger (up to 2.5) than those obtained in our calculation.…”
Section: Comparison To Experimentssupporting
confidence: 51%
“…Given the theoretical arguments [3,4], this constitutes direct experimental evidence for the presence of topological order. In the hole-doped cuprates, Hall effect measurements [7] on YBa 2 Cu 3 O y indicate a small Fermi surface at near optimal hole densities without any density wave order, and the doping dependence of the Hall co-efficient fits well a theory of Fermi surface reconstruction by topological order [8,9]. Also in YBa 2 Cu 3 O y , but at lower hole-doping, quantum oscillations have been observed, and are likely in a region where there is translational symmetry breaking due to density wave order [10]; however, the quantum oscillation [11] and specific heat [12] observations indicate the presence of only a single electron pocket, and these are difficult to understand in a model without prior Fermi surface reconstruction [13] (and pseudogap formation) due to topological order.…”
Section: Introductionmentioning
confidence: 58%